Marfan's syndrome and the heart - Stuart, Alan Graham (BMJ Group, 2007)
In recent years, there have been many advances in the treatment of cardiac disease in children with Marfan's syndrome. Early diagnosis, meticulous echocardiographic follow‐up and multidisciplinary assessment are essential. Medical treatment with β‐blockers is probably helpful in most children with aortic root dilatation. Research on TGFβ signalling and the potential treatment role of TGFβ antagonists may lead to exciting new treatments, but the results of clinical trials are awaited. In managing the cardiovascular complications of Marfan's syndrome, the paediatrician has to walk a difficult path. On the one hand, restrictive lifestyle advice and drugs may need to be prescribed, often in the context of a family history of major surgery or even sudden death. On the other hand, it is essential to encourage the often asymptomatic child to develop and mature as normally as possible.